Primary mediastinal large B‐cell lymphoma is characterized by large‐scale copy‐neutral loss of heterozygosity. Issue 10 (9th July 2022) - Tuveri, Stefania; Debackere, Koen; Marcelis, Lukas; Dierckxsens, Nicolas; Demeulemeester, Jonas; Dimitriadou, Eftychia; Dierickx, Daan; Lefesvre, Pierre; Deraedt, Karen; Graux, Carlos; Michaux, Lucienne; Cools, Jan; et al.
Abstract: Development of primary mediastinal B‐cell lymphoma (PMBL) is driven by cumulative genomic aberrations. We discovered a unique copy‐neutral loss of heterozygosity (CN‐LOH) landscape of PMBL which distinguishes this tumor from other B‐cell malignancies, including the biologically related diffuse large B‐cell lymphoma. Using single nucleotide polymorphism array analysis we identified large‐scale CN‐LOH lesions in 91% (30/33) of diagnostic PMBLs and both investigated PMBL‐derived cell lines. Altogether, the cohort showed 157 extra‐large (25.3–248.4 Mb) CN‐LOH lesions affecting up to 14 chromosomes per case (mean of 4.4) and resulting in a reduction of heterozygosity an average of 9.9% (range 1.3–51%) of the genome. Predominant involvement of terminal chromosomal segments suggests the implication of B‐cell specific crossover events in the pathogenesis of PMBL. Notably, CN‐LOH stretches non‐randomly clustered on 6p (60%), 15 (37.2%), and 17q (40%), and frequently co‐occurred with homozygous mutations in the MHC I (6p21), B2M (15q15), and GNA13 (17q23) genes, respectively, as shown by preliminary whole‐exome/genome sequencing data. Altogether, our findings implicate CN‐LOH as a novel and distinct mutational process contributing to the molecular pathogenesis of PMBL. The aberration acting as "second hit" in the Knudson hypothesis, ranks as the major mechanism converting to homozygosity the PMBL‐related driver genes. Screening of the cohort of 199 B cell leukemia/lymphoma whole‐genomes revealed significant differences in the CN‐LOH landscape of PMBL and other B‐cell malignancies, including the biologically related diffuse large B‐cell lymphoma.